Study of OH- Radicals in Human Serum Blood of Healthy Individuals and Those with Pathological Schizophrenia - Korotkova E. I. Elena Ivanovna; Dorozhko E. V. Elena Vladimirovna; Bukkel M. V.; Plotnikov E. V. Evgeny Vladimirovich; Misini B.; Linert W. (2011, 2011)
The human body is constantly under attack from free radicals that occur as part of normal cell metabolism, and by exposure to environmental factors such as UV light, cigarette smoke, environmental pollutants and gamma radiation. The resulting "Reactive Oxygen Species" (ROS) circulate freely in the body with access to all organs and tissues, which can have serious repercussions throughout the body. The body possesses a number of mechanisms both to control the production of ROS and to cope with free radicals in order to limit or repair damage to tissues. Overproduction of ROS or insufficient defense mechanisms leads to a dangerous disbalance in the organism. Thereby several pathomechanisms implicated in over 100 human diseases, e.g., cardiovascular disease, cancer, diabetes mellitus, physiological disease, aging, etc., can be induced. Thus, a detailed investigation on the quantity of oxygen radicals, such as hydroxyl radicals (OHfilled circle) in human serum blood, and its possible correlation with antioxidant therapy effects, is highly topical. The subject of this study was the influence of schizophrenia on the amount of OHfilled circle in human serum blood. The radicals were detected by fluorimetry, using terephthalic acid as a chemical trap. For all experiments the serum blood of healthy peop le was used as a control group. © 2010 by the authors; licensee MDPI, Basel, Switzerland.